Fuguai Mapping: The Useful Method For Problem Solving - Wan Mahmood, Wan Hasrulnizzam; Abdullah, Ilyana (Penerbit Universiti, Universiti Teknikal Malaysia Melaka, 2008)
Fuguai in Japanese word also called abnormality. The abnormality is unneeded thing which located at the wrong places or situations. In most conditions, the abnormality affected physical, functional and safety problems especially for machines. This paper discusses the application of Fuguai Mapping in order to identify the abnormality at grinding machine as a preventive action to sustain the machine condition. Through the study, it shows that many abnormalities were found. As a result, most of the abnormalities at machine were reduced and had improved the machine efficiency.